The Role of Citizens in Socializing the Effectiveness of Vaccines to Support National Health Development - Juliana Tirza (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Basic Health Research data in 2018 shows that the coverage of Complete Basic Immunization (IDL) reaches 57.9%, incomplete immunization is 32.9%, and 9.2% is not immunized (Kemenkes RI, 2018). It is estimated that 1.7 million deaths that occur in children under five in Indonesia are the result of PD3I. This study aims to determine the factors that influence Indonesia's immunization rates and the role of citizens in it. This paper aims to determine what factors influence Indonesia's immunization rate and the part of citizens in it. Another objective is to assess citizens' role in immunization rates in Indonesia to determine the factors that influence the immunization rate of the people in Indonesia. This study used a descriptive qualitative method. The effectiveness of the immunization program in Indonesia itself has again been proven from year to year, also every citizen is strongly encouraged to complete the basic immunization program. Therefore, Health Law number 36 of 2009 states that every child has the right to receive necessary immunization to prevent diseases that can be avoided through vaccination. The government is obliged to provide complete immunization to every baby and child. Full primary immunization (IDL) can be influenced by several factors, such as the level of parental knowledge about vaccination, parental motivation, and socio-cultural factors and parental beliefs. Benefits of the immunization program must be supported by citizens through educate the society about the effectiveness of Vaccines especially for children.